Superior Culinary Products Maninjau Wisata West Sumatra Province - Winara, Bahgia; Yuliana, Yuliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This study aims to analyze the superior culinary products of Maninjau Tourism Village from the indicators of the type of product processing, product packaging and product marketing. This research uses a descriptive approach with qualitative data. Data sources were obtained from the Tourism, Youth and Sports Office of Agam Regency, Tanjung Raya Sub- District Head, Maninjau Nagari Wali, Traditional/Religious Leaders, Culinary Traders and Visitors/Tourists. Data collection was carried out directly in Nagari Maninjau using interview, observation and documentation methods. Data analysis was carried out using data reduction techniques, data presentation and drawing conclusions. The results of the study found that the superior culinary products of the Maninjau Tourism Village were processed rinuak fish, bada fish and pensi. Processed forms are rinuak fritters, rinuak crackers, rinuak jerky, rinuak palai, crispy rinuak, rinuak rakik, fried bada, bada smoked and pensi soup. While the packaging  uses transparent plastic and leaves. Then the marketing is still conventional. This superior culinary product of the Maninjau Tourism Village has the potential to be developed further both in the form of processed products, product packaging and product marketing.